What is the optimum thiamine dose to treat or prevent Wernicke's encephalopathy or Wernicke–Korsakoff syndrome? Results of a randomized controlled trial. (10th May 2022) - Dingwall, Kylie M.; Delima, Jennifer F.; Binks, Paula; Batey, Robert; Bowden, Stephen C.
Abstract: Background: The primary cause of Wernicke–Korsakoff syndrome (WKS) is thiamine deficiency, and more than 90% of cases are reported in alcohol‐dependent patients. While observational studies show parenteral thiamine administration drastically reduced WKS‐related mortality, relevant treatment trials have never been conducted to determine the optimum thiamine dose. Methods: Two double‐blind, parallel groups, randomized controlled trials (RCTs) were conducted to determine the optimal thiamine dose required for (1) the prevention of Wernicke's encephalopathy (WE), the acute phase of WKS, in asymptomatic but "at‐risk" alcohol misuse patients (Study 1) and (2) the treatment of WE in symptomatic alcohol misuse patients (Study 2). Each study had a dosage regimen comprising three parenteral thiamine doses that were allocated at a ratio of 1:1:1. Study 1: Asymptomatic At‐Risk patients ( N  = 393) received either 100 mg daily, 100 mg thrice daily, or 300 mg thrice daily, for 3 days. Study 2: Symptomatic patients ( N  = 127) received either 100 mg thrice daily, 300 mg thrice daily, or 500 mg thrice daily, for 5 days. Cognitive function was the primary outcome, assessed using the Rowland Universal Dementia Assessment Scale, two Cogstate subtests, and an adapted Story Memory Recall test. Secondary analyses examined differences in neurological function (ataxia, oculomotor abnormalities, and confusion) at follow‐up. Results: No significant differences were observed between any of the dosage conditions for either Study 1 or Study 2 on cognition or neurological functioning. This real‐world study found that having a clinically unwell target population with high comorbidity and multiple presentations, coupled with challenges in cross‐cultural assessment is likely to complicate RCT findings. Conclusions: The results of this study showed no clear benefit of high dose thiamine over intermediate or lower doses of thiamine, over the time intervals examined, for the treatment and prevention of cognitive and neurological abnormalities related to WKS. Several study limitations temper the interpretation of these findings. Nevertheless, the absence of conclusive evidence for the superiority of high‐dose thiamine supports a recommendation for patient‐specific treatment, while ensuring that the potential impact of other biochemical factors (e.g., magnesium and other B vitamin deficiencies) are considered and corrected if necessary. Abstract : Two randomised controlled trials examined differences in cognitive or neurological response to varied thiamine dose regimens for 1) treatment of acute Wernicke Korsakoff's Syndrome and 2) the prevention of WKS in asymptomatic but at‐risk patients. Low, intermediate, and high doses of thiamine were examined for each patient group. The study found no benefit of high dose thiamine over intermediate or lower doses. Thiamine dose should be patient specific and include investigation of co‐morbidities that may impact thiamine replacement (e.g. hypomagnesemia).